Análise numérica de uma ligação mista viga-pilar com chapa passante - Santos, Tiago José dos (2014)
Among all of the existing structural systems, the steel-concrete composite elements outstands because it takes advantage of the properties of both materials in the same element. Unlike the system in reinforced concrete cast in situ, the steel-concrete composite system is not monolithic, and therefore the global behavior of the structure is mainly linked to the behavior of the connections. Currently, the beam-column connections have been the subject of theoretical and experimental studies to better understand their structural behavior. This concern has become even bigger with the introduction of requirements on steel-concrete composite connections in the Brazilian standard ABNT NBR 8800:2008. In order to contribute to this subject, in this work is studied by numerical modeling, a detail of a composite beam-column connection with shear plate using numerical models. The numerical analysis performed in the computer package ANSYS® was divided in two phases: validation of the numerical model from experimental results and subsequent parametric analysis. Despite of the simplifications adopted in the numerical simulation, the results were satisfactory and representative of the experimental behavior, especially for Force vs. Displacement at the end of the beam. Once validated the numerical model, a parametric study was conducted in order to evaluate the influence of some parameters on the bearing capacity of connections, such as the concrete slab reinforcement ratio, the slab thickness and the steel beam depth. The results of the parametric analysis showed that the variation of the slab thickness was the parameter with more influence on the bearing capacity of the composite connection with shear plate.